Electrochemical Method for Studying Localized Corrosion beneath Disbonded Coatings under Cathodic Protection. Issue 10 (1st January 2015) - Varela, F.; Tan, M. YJ.; Forsyth, M.
Abstract : This paper presents a new method for measuring localized corrosion under disbonded coatings by means of an electrochemical sensor, denoted differential aeration sensor (DAS). It measures the distribution of electrochemical currents over an electrode array surface partially covered by a crevice that simulates a disbonded coating. The DAS has been evaluated using immersion tests at open circuit and under cathodic protection (CP) conditions. Under both conditions, anodic as well as cathodic current densities were detected within the crevice. A fundamental understanding for the detection of anodic currents under CP has been explained in terms of basic electrochemistry. Based on the current distribution data provided by the sensor, two different analysis methods have been used to estimate corrosion and its distribution. These methods consisted of a direct application of Faraday's Law to the anodic currents detected by the array, and on a sensor-specific method denoted ' corrected currents' method. It has been demonstrated that under diffusion controlled conditions this latter method produces a better corrosion estimation than the direct application of Faraday's Law. The 'corrected currents' method allowed the estimation of corrosion patterns outside the crevice under CP. Good correlation between electrochemical calculations and surface profilometry results has been obtained.